Applicability of the Reinforced Ground Embankments on Sloped Terrain and Their Comparison with Alternative Rockfall Protection System Solutions: Kanlıpelit Case - Muhammet Çelik; Mohammad Manzoor Nasery (Doğal Afetler ve Çevre Dergisi)
Reinforced ground embankments having high energy absorption capacity, which are being used as rockfall protection systems, are massive structures. Various problems arise in the application of reinforced ground embankments on sloped terrain, where rockfall occurs, because of it is high bottom width. In this study, a solution was improved for the application of reinforced ground embankments walls on sloping lands and was examined by implementing a pilot project. Additionally, it was planned to obtain a flat platform on inclined land with a 6 m high stone retaining wall and filling in order to construct the reinforced ground embankments wall on it. Initially rock fall analyses were performed on 8 cross sections in order to obtain bounce height, velocity and total kinetic energy values prior to constructing the platform. The same analysis was once again performed following the platform construction and the obtained data were compared. This platform has reduced 83% of the rocks’ bounce heights, 62% of kinetic energy and 42% of velocity values. In the second part of the study, the cost of the reinforced ground embankments on the platform was compared with the costs of alternative projects. It was observed that constructing platform was 60.8% less expensive than a 6meter reinforced concrete wall with a 3meter steel barrier and 74.5% cheaper than a 6meter steel barrier. Steel barriers are disadvantageous compared to the reinforced ground embankments walls in various aspect such as reduction in length during rock collisions, construction cost, maintenance costs, import and adaptation to nature. For the reasons above, we have concluded that construction of reinforced ground embankments wall over a constructed platform is a more efficient improvement solution in terms of both safety and cost. The developed solution within the scope of the study was applied in the rockfall protection project in Güney neighborhood, Maçka District of Trabzon Province.